AGO recommendations for the surgical therapy of breast cancer - update 2022 = AGO-Empfehlungen zur operativen Therapie des Mammakarzinoms - Update 2022 - Banys-Paluchowski, Maggie; Heil, Jörg; Schneeweiss, Andreas; Sinn, Peter; Thomssen, Christoph (Geburtshilfe und Frauenheilkunde, 2022)
The recommendations of the AGO Breast Committee on the surgical therapy of breast cancer were last updated in March 2022 (www.ago-online.de). Since surgical therapy is one of several partial steps in the treatment of breast cancer, extensive diagnostic and oncological expertise of a breast surgeon and good interdisciplinary cooperation with diagnostic radiologists is of great importance. The most important changes concern localization techniques, resection margins, axillary management in the neoadjuvant setting and the evaluation of the meshes in reconstructive surgery. Based on meta-analyses of randomized studies, the level of recommendation of an intraoperative breast ultrasound for the localization of non-palpable lesions was elevated to “”. Thus, the technique is considered to be equivalent to wire localization, provided that it is a lesion which can be well represented by sonography, the surgeon has extensive experience in breast ultrasound and has access to a suitable ultrasound device during the operation. In invasive breast cancer, the aim is to reach negative resection margins (“no tumor on ink”), regardless of whether an extensive intraductal component is present or not. Oncoplastic operations can also replace a mastectomy in selected cases due to the large number of existing techniques, and are equivalent to segmental resection in terms of oncological safety at comparable rates of complications. Sentinel node excision is recommended for patients with cN0 status receiving neoadjuvant chemotherapy after completion of chemotherapy. Minimally invasive biopsy is recommended for initially suspect lymph nodes. After neoadjuvant chemotherapy, patients with initially 1 - 3 suspicious lymph nodes and a good response (ycN0) can receive the targeted axillary dissection and the axillary dissection as equivalent options.
Gesehen am 31.01.2023